Thickness Dependence of Thermoelectric Properties and Maximum Output Power of Single Planar Sb2Te3 Films - Prasopporn Junlabhut; Pilaipon Nuthongkum; Adul Harnwunggmoung; Pichet Limsuwan; Chanon Hatayothai; Rachsak Sakdanuphab; Aparporn Sakulkalavek (Materials, 2022)
produced a maximum output power of 0.032 µW for a temperature difference of 58 K.
Keywords: Advanced Thermoelectric Materials and Devices; Chalcogenide Semiconductor Thin Films; Thermal Radiation and Cooling Technologies